Does substance abuse contribute to further risk of falls in dementia - Eshkoor, Sima Ataollahi; Hamid, Tengku Aizan; Hassan Nudin, Siti Sa'adiah; Chan, Yoke Mun (Taylor & Francis, 2014)
This study aimed to predict the risk of falls by focusing on substance abuse in the elderly with dementia. Our national cross-sectional survey included 1210 elderly Malaysian demented subjects. The study identified the effects of age, ethnicity, sex differences, marital status, educational level, and substance abuse on the likelihood of falls in the elderly with dementia. The multivariate logistic regression model was used to analyze data collected from samples. The prevalence of falls was about 17% among subjects and significantly increased with age (p = .006). Furthermore, the results showed that age (OR = 1.03), ethnicity (OR = 1.69), substance abuse (OR = 1.68), and female sex (OR = 1.45) significantly enhanced the risk of falls in respondents (p < .05). Educational level and marital status had no significant effects on the likelihood of falls (p > .05). However, the findings provided evidence of an additional effect of substance abuse on further risk of falls in older adults with dementia.